2020
DOI: 10.1101/2020.09.18.304048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronic Psychosocial Stress and Experimental Pubertal Delay Affect Socioemotional Behavior and Amygdala Functional Connectivity in Adolescent Female Rhesus Macaques

Abstract: In females, pubertal onset appears to signal the opening of a window of increased vulnerability to the effects of stress on neurobehavioral development. What is the impact of pubertal timing on this process? We assessed the effects of pubertal timing and stress on behavior and amygdala functional connectivity (FC) in adolescent female macaques, whose social hierarchy provides an ethologically valid model of chronic psychosocial stress. Monkeys experienced puberty spontaneously (n=34) or pubertal delay via Lupr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In male sheep, impairments in spatial memory associated with the treatment were not fully reversed following discontinuation of treatment 51 . Significant effects of treatment were also evident on measures of brain structure including overall volume 53 , functional connectivity 52 and neuronal density 54 .…”
Section: Performance On Cognitive Tasks (Maze Tasks)mentioning
confidence: 97%
See 1 more Smart Citation
“…In male sheep, impairments in spatial memory associated with the treatment were not fully reversed following discontinuation of treatment 51 . Significant effects of treatment were also evident on measures of brain structure including overall volume 53 , functional connectivity 52 and neuronal density 54 .…”
Section: Performance On Cognitive Tasks (Maze Tasks)mentioning
confidence: 97%
“…The majority of these studies (n=8) have been conducted in the same flock of sheep using twin controls 10,11,[46][47][48][49][50][51] . Two studies in monkeys 52,53 and one mouse study 54 were also identified. Measures of brain structure were reported in 5 studies and included structural MRI, resting state functional MRI and histopathology (see Table 1).…”
Section: Animal Studiesmentioning
confidence: 99%
“…In male sheep, impairments in spatial memory associated with the treatment were not fully reversed following discontinuation of treatment 51 . Significant effects of treatment were also evident on measures of brain structure including overall volume 53 , functional connectivity 52 and neuronal density 54 .…”
Section: Performance On Cognitive Tasks (Maze Tasks)mentioning
confidence: 97%
“…The majority of these studies (n=8) have been conducted in the same flock of sheep using twin controls 10,11,[46][47][48][49][50][51] . Two studies in monkeys 52,53 and one mouse study 54 were also identified. Measures of brain structure were reported in 5 studies and included structural MRI, resting state functional MRI and histopathology (see Table 1).…”
Section: Animal Studiesmentioning
confidence: 99%